2010
DOI: 10.1177/0003319710379108
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Contrast-Induced Nephropathy and Cardiovascular Events by Serum Cystatin C in Renal Insufficiency Patients Undergoing Cardiac Catheterization

Abstract: We assessed the usefulness of serum cystatin C for predicting contrast-induced nephropathy (CIN) in patients (n = 100) undergoing coronary catheterization. After a 12-month follow-up, the incidence of CIN was 8.3% (n = 5) in patients with mild renal insufficiency (estimated glomerular filtration rate [eGFR] 60-89 mL/min per 1.73 m²), 34.4% (n = 10) in those with moderate renal insufficiency (eGFR 30-59 mL/min per 1.73 m²), and 100% (n = 3) in those with severe renal insufficiency (eGFR 15-29 mL/min per 1.73 m²… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 38 publications
(39 reference statements)
0
35
1
Order By: Relevance
“…Its structure is not affected by inflammation, dietary factors, sex, age or muscle mass [11,12,13]. Several studies examined the role of cystatin C in predicting CIN [14,15,16,17,18]. Ebru et al [14] showed that only cystatin C increase after contrast media exposure is in concordance with the Mehran risk scoring system for predicting the risk of CIN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its structure is not affected by inflammation, dietary factors, sex, age or muscle mass [11,12,13]. Several studies examined the role of cystatin C in predicting CIN [14,15,16,17,18]. Ebru et al [14] showed that only cystatin C increase after contrast media exposure is in concordance with the Mehran risk scoring system for predicting the risk of CIN.…”
Section: Discussionmentioning
confidence: 99%
“…Ebru et al [14] showed that only cystatin C increase after contrast media exposure is in concordance with the Mehran risk scoring system for predicting the risk of CIN. Another study found that baseline serum cystatin C levels significantly predicted the occurrence of CIN in patients with moderate renal insufficiency [15]. A study from Germany demonstrated that CIN was predicted by baseline cystatin C, whereas creatinine, creatinine clearance and blood urea nitrogen were not predictive [16].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that serum cystatin C may predict CIN in patients with moderate renal insufficiency undergoing cardiac catheterization [5]. This "marker" may help identify patients where additional measures (e.g.…”
mentioning
confidence: 99%
“…Although several studies have revealed that serum cystatin C cut off level >1.2 or >1.18 or >1.3 mg/l, 94% sensitivity and 48% specificity is more accurate for diagnostic CIN than serum creatinine [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. While study obtained by Ribichini et al found that absolute changes in serum creatinine proved more accurate than serum cystatin C for predicting CIN at an early stage 12 hours after angiography [18].…”
Section: Discussionmentioning
confidence: 99%